2005
DOI: 10.1523/jneurosci.0925-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Dorsal Striatum in Cue-Controlled Cocaine Seeking

Abstract: Through association with the interoceptive effects of drugs of abuse, neutral environmental stimuli can gain motivational properties themselves, becoming conditioned reinforcers that can evoke craving and relapse to drug seeking. Nucleus accumbens dopamine (DA) neurotransmission plays an important role in the reinforcing effect of cocaine itself, but, unlike nucleus accumbens glutamate, it seems not to mediate the conditioned reinforcing properties of cocaine-paired stimuli. Dorsal striatal DA transmission, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
270
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 350 publications
(313 citation statements)
references
References 80 publications
40
270
2
1
Order By: Relevance
“…In contrast, cocaine intake (reinforced nose pokes) was increased by the antagonist in both the first and third weeks, suggesting that this effect likely is not associated with the phasic modality of dopamine signaling time-locked to drug taking, and therefore tonic dopamine signaling may be implicated. This notion is consistent with the work of others indicating a role for DLS dopamine in mediating the reinforcing properties of cocaine (21,22). Therefore, rather than contributing to escalated or compulsive responding, the progressive recruitment of DLS phasic dopamine promotes the refinement of behavior toward reinforced actions, as operant responding for the drug becomes more reliably discriminated over the course of weeks in the absence of escalated drug intake.…”
Section: Dopamine Signaling In the Sensorimotor Striatum Emerges Beforesupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast, cocaine intake (reinforced nose pokes) was increased by the antagonist in both the first and third weeks, suggesting that this effect likely is not associated with the phasic modality of dopamine signaling time-locked to drug taking, and therefore tonic dopamine signaling may be implicated. This notion is consistent with the work of others indicating a role for DLS dopamine in mediating the reinforcing properties of cocaine (21,22). Therefore, rather than contributing to escalated or compulsive responding, the progressive recruitment of DLS phasic dopamine promotes the refinement of behavior toward reinforced actions, as operant responding for the drug becomes more reliably discriminated over the course of weeks in the absence of escalated drug intake.…”
Section: Dopamine Signaling In the Sensorimotor Striatum Emerges Beforesupporting
confidence: 91%
“…Intra-DLS infusion of flupenthixol resulted in an increase in cocaine intake (reinforced nose pokes) at both the early and late time points (P < 0.05 vs. vehicle; Fig. 4D), suggesting that DLS dopamine may contribute to the reinforcing properties of cocaine, as is consistent with previous reports (21,22). Importantly, this effect therefore is not attributable to the CS-associated phasic dopamine signal, which was present at the late time point but not the early time point.…”
Section: Dopamine Receptors In the Dls Are Necessary For Discriminatedsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, our results suggest that glutamate transmission in the caudateputamen is not involved in context-induced reinstatement. However, this conclusion is tentative because our injections targeted the ventral part of the caudate-putamen; it was recently reported that blockade of AMPA receptors in the dorsal caudate-putamen attenuates discrete cue-controlled cocaine seeking (Vanderschuren et al, 2005), but see Kantak et al (2002) for different results.…”
Section: Discussionmentioning
confidence: 83%
“…We also studied the effect of LY379268 on context-induced reinstatement after injections into the nearby caudate-putamen, a terminal region of the nigrastriatal dopamine system. The caudate-putamen is known to be involved in stimulus-response learning White and McDonald, 2002), and data from two studies indicate that both dopamine and glutamate in this brain area are involved in cue-controlled cocaine seeking (Ito et al, 2002;Vanderschuren et al, 2005). Additionally, we tested the effect of injections of LY379268 into the NAc core or shell on high rates of lever responding for sucrose in order to rule out the possibility that these injections decrease context-induced reinstatement due to their motor impairing effects on lever pressing.…”
Section: Introductionmentioning
confidence: 99%